NUMERICAL RESEARCH ON BUILDING VENTILATION SPACE IN THE LAYOUTS OF RESIDENTIAL AREA - Xiaoyu Ying; Wei Zhu; Kazunori Hokao (Lowland Technology International, 2014)
Building density in a master plan directly affects the outdoor physical environmental quality in residential area. Inappropriate design of a layout may cause impact on external comfort, such as lack of air movement. To tackle this problem, a dimensional variable, named as ventilation space was defined to feature the building density in a master plan. It consists of the gable space and fore-and-aft space. The Reynolds averaged equations and the renormalization group (RNG) κ-ε turbulence model was used to simulate the wind condition in some typical layouts under the weather condition in Hangzhou, China. The simulated wind conditions were assessed using the criteria, the wind speed ratio at some key locations on pedestrian level. The effects of the ventilation space on the air movement were discussed and an optimal space was derived for each of the modeled layouts. The set of results were expected to be used as a rule of thumb by architects and planners in master planning stage.